Philippine government directory (The Office, 1984)
"This directory lists the offices under the Executive Branch of the Government including the lists attached to or directly under the Office of the President, the line departments as well as their bureaus and agencies. It also includes the legislative and judicial departments of government, the Constitutional Commission, government-owned, and controlled corporations, the government financial institutions, local officials from the provincial, municipal level, and the diplomatic and consular offices of foreign countries in the Philippines. It also presents a comprehensive list of telephone numbers and major officials in these offices." Includes an index.